2016
DOI: 10.1161/circresaha.116.308501
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 Inflammasome Activation Mediates Homocysteine-Induced Pyrop-Apoptosis in Endothelial Cells

Abstract: Rationale Endothelial injury is an initial mechanism mediating cardiovascular disease. Objective Here, we investigated the effect of hyperhomocysteinemia (HHcy) on programed cell death in endothelial cells (EC). Methods and Results We established a novel flow-cytometric gating method to define pyrotosis (Annexin V−/Propidium iodide+). In cultured human EC, we found that: 1). Hcy and Lipopolysaccharide (LPS) individually and synergistically induced inflammatory pyroptotic and non-inflammatory apoptotic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
156
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 56 publications
8
156
0
Order By: Relevance
“…Therefore, it was hypothesized that NLRP3 was a potential target gene of miR-22, which was further confirmed by the results from the dual-luciferase reporter assays. Caspase-1 activation induced EC dysfunction, leading to vascular remodeling and atherosclerosis [26]. Similarly, Li et al also demonstrated that miR-20a over-expression reduced the formation of the NLRP3 inflammasome, including reducing NLRP3 and caspase-1 expression [27], which possibly explains how miR-22 expression is related to NLRP3 and caspase-1 in our study.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, it was hypothesized that NLRP3 was a potential target gene of miR-22, which was further confirmed by the results from the dual-luciferase reporter assays. Caspase-1 activation induced EC dysfunction, leading to vascular remodeling and atherosclerosis [26]. Similarly, Li et al also demonstrated that miR-20a over-expression reduced the formation of the NLRP3 inflammasome, including reducing NLRP3 and caspase-1 expression [27], which possibly explains how miR-22 expression is related to NLRP3 and caspase-1 in our study.…”
Section: Discussionsupporting
confidence: 71%
“…This was further validated by the recent reports from our lab, which demonstrated that NLR/ caspase-1 signaling pathway is responsible for inducing endothelial activation and subsequent atherogenesis during early hyperlipidemia [58] and hyperhomocysteinemia [63], for decreasing vascular endothelial growth factor receptor 2 (VEGFR2) mediated angiogenesis in ischemia [64], and for weakening of the progenitor cell mediated vessel repair [3,64]. …”
Section: Discussionmentioning
confidence: 57%
“…EC death triggered by lipopolysaccharide (LPS) and tumor necrosis factor α (TNFα) has been determined in septic mice 9,10 . Studies have shown that LPS through activating caspase-1 induces EC pyroptosis 11 , a caspase-1-dependent pro-inflammatory cell death type 12 . Cell pyroptosis, which can be triggered by various pathological stimuli, including infection, is characterized by plasma-membrane pore formation, intracellular content release, and DNA cleavage 12,13 .…”
Section: Introductionmentioning
confidence: 99%